Drug use, sexual risk, and structural vulnerability among female sex workers in two urban centers of the Dominican Republic: The EPIC study. (1st July 2020) - Pérez-Figueroa, R.; Mittal, I.; Halpern, M.; Pérez-Mencia, M.; Donastorg, Y.; Taylor, B.S.; Amesty, S.
Highlights: We examined drug use among female sex workers in the Dominican Republic. Sexual risk was associated with marijuana and crack/cocaine use. Being socially disadvantaged was correlated with marijuana and crack/cocaine use. Further research must emphasize FSWs' social and economic environment. Abstract: Background: Evidence in different countries suggest an association between sex work and drug use. In the Dominican Republic an estimated 60, 000–100, 000 women work in the sex industry. However, little is known about their drug use behaviors. Objective: To characterize the burden of drug use and examine correlates of these behaviors among female sex workers in the Dominican Republic. Methods: Data for this analysis comes from a cross-sectional study among key populations at risk for HIV. A community sample of female sex workers (N = 389) was recruited using passive and active recruitment strategies. Participants completed a behavioral survey between 2015 and 2016. Logistic regression models were constructed to examine predictors of drug use. Results: Protective factors against marijuana and crack or cocaine use included being heterosexual, having a higher level of education, regular employment, and fewer male sexual partners. Increased odds of crack or cocaine use were associated with incarceration, having slept in a place not meant for human habitation in the last six months, and having ever lived in a batey (a community around a sugar mill where workers and their families live). Participants that used marijuana were generally younger, while those that used crack or cocaine were older. Conclusions: Our findings highlight characteristics of the social and economic environment that require further research to optimize prevention and care strategies for this population. Public health interventions are needed that address drug use, sexual risk-taking, and helping female sex workers and their families achieve a healthy life.